The Assessment of Student Doctors’ attitude towards disabled people after teaching them a module: The Assessment of Student Doctors’ attitude towards disabled people - arabi, hafid; Adarmouch, latifa; Ahmed Eladip, ghassan (Acta Biomedica Atenei Parmensis, 2021)
Objective: Assessing the attitude of medical students towards people with disabilities after teaching them a disability module.Methods: Several themes were taught. To assess the attitude of disability before and after the course, we used the ATDP (Attitude towards disabled persons) scale after translating it from English into Classical Arabic using the translation-back translation method.Results: 250 students benefited from this course. 78 of them were subjected to evaluation, including 20 male students (25.64%) and 58 female students (74.35%). There was no significant difference in the ATDP score between before and after among boys (before 72 (66.75-81.5) vs 72 (66, 81.5) after, p: 0.32). Among girls, there was a decrease in the ATDP score (74 (67.5-83.25) vs 70 (65-80.25), p: 0.03). No significant difference was found according to gender before and after. The ATDP construct validation in classical Arabic had a Cronbach's alpha of 0.60. The test-retest (ICC) 0.825.Conclusion: Although the perception towards disabled people has negatively changed among girls and while unchangeable within boys, this disability module in our faculty was a first experience in Morocco. It would be desirable to develop other educational methods in this subject matter.